Asteroseismic Study of KUV03442+0719 with Parallax Constraints - Agnes Bischoff-Kim (The Astrophysical Journal, 2023)
Hydrogen atmosphere white dwarf KUV03442+0719 was first reported as a pulsator by Gianninas et al. in 2006. Follow-up campaigns by Su et al. revealed more periods. Some spectroscopic results suggest that KUV03442+0719 has a slightly below-average mass and an effective temperature of 11,000 K. However, Gaia data (parallax and magnitude) suggest that it may be a low-mass white dwarf. Such an object would have a helium core. We perform asteroseismic fitting of KUV03442+0719, modeling it both as a carbon/oxygen normal mass white dwarf, and a helium-core low-mass white dwarf. To perform the study, we perform a grid search with WDEC models, refined by simplex minimization of the best fits. Both analyses result in best-fit models that are comparable in terms of quality of fit. More pulsation data would be required to allow us to distinguish between the two scenarios. We present and contrast our results with expectations from stellar evolution. We also provide analytic formulae for a temperature-dependent mass–radius relationship for helium-core white dwarfs.